Bloody fluids located between the temporal muscle and targeted cerebral cortex affect the establishment of indirect collaterals in Moyamoya disease with surgical bypass: A case-control study - Li, Yin; Hu, Jun-wen; He, Xu-chao; Cao, Yang; Yu, Xiao-bo; Fu, Xiong-jie; Zhou, Hang; Hu, Li-bin; Xu, Liang; Xu, Chao-ran; Wang, Yong-jie; Wang, Lin (Frontiers in Neurology, 2022)
Objective: Bypass yields favorable outcomes in treating moyamoya disease (MMD). Bloody fluids accumulate between the targeted cortex and temporal muscle after surgical bypass. These fluids are handled empirically either via subcutaneous tubes or conservative treatments. However, substances located in certain positions may adversely affect establishing indirect collaterals from muscular grafts. Methods: Patients at our hospital from January 2014 to December 2019 were eligible for inclusion. Digital subtraction angiography (DSA) and radiological examinations were used during the perioperative and follow-up periods. Bloody fluid volumes were calculated using 3D Slicer software based on computed tomography. Characteristics of the bloody fluids, patient demographics, and clinical data were retrospectively analyzed. Results: One hundred ten patients underwent indirect or combined bypass with follow-up DSA. The mean age of the enrolled patients was 42.4 ± 11.8 years. Previous ischemia (P = 0.001), previous hemorrhaging (P = 0.013), bloody fluid volume (P = 0.049) and time of imaging (P = 0.081) were associated with indirect outcomes. Ordinal regression analysis confirmed that good indirect outcomes were associated with previous ischemia (P < 0.001) and large bloody fluid volume (P = 0.013). Further subgroups based on fluid volume were significantly correlated with indirect collateral establishment (P = 0.030). Conclusions: Large bloody fluid volume and previous ischemic history were associated with good indirect outcomes. Presence of bloody fluids may reflect impaired degrees of muscular donors owing to bipolar electrocoagulation, thus highlighting the importance of appropriate application of bipolar forceps.